A Case of Lassa Fever Diagnosed at a Community Hospital—Minnesota 2014. (16th July 2018) - Choi, Mary J; Worku, Shewangizaw; Knust, Barbara; Vang, Arnold; Lynfield, Ruth; Mount, Mark R; Objio, Tina; Brown, Shelley; Griffith, Jayne; Hulbert, Deborah; Lippold, Susan; Ervin, Elizabeth; et al.
Abstract: Background: In April 2014, a 46-year-old returning traveler from Liberia was transported by emergency medical services to a community hospital in Minnesota with fever and altered mental status. Twenty-four hours later, he developed gingival bleeding. Blood samples tested positive for Lassa fever RNA by reverse transcriptase polymerase chain reaction. Methods: Blood and urine samples were obtained from the patient and tested for evidence of Lassa fever virus infection. Hospital infection control personnel and health department personnel reviewed infection control practices with health care personnel. In addition to standard precautions, infection control measures were upgraded to include contact, droplet, and airborne precautions. State and federal public health officials conducted contract tracing activities among family contacts, health care personnel, and fellow airline travelers. Results: The patient was discharged from the hospital after 14 days. However, his recovery was complicated by the development of near complete bilateral sensorineural hearing loss. Lassa virus RNA continued to be detected in his urine for several weeks after hospital discharge. State and federal public health authorities identified and monitored individuals who had contact with the patient while he was ill. No secondary cases of Lassa fever were identified among 75 contacts. Conclusions: Given the nonspecific presentation of viral hemorrhagic fevers, isolation of ill travelers and consistent implementation of basic infection control measures are key to preventing secondary transmission. When consistently applied, these measures can prevent secondary transmission even if travel history information is not obtained, not immediately available, or the diagnosis of a viral hemorrhagic fever is delayed.